The Impact Of Political Decisions Within The WTO Dispute Settlement System: Political Negotiations Within Adjudication - Gebeyehu, Meaza Haddis (UI Scholars Hub, 2019)
It is traditionally contended that politics and law are two separate domains of international relations among the main actors, states. As opposed to this thinking, international relations of the twenty-first century have been characterized by the continuing interaction of law and politics. As the main actors and participants in international law, states played and still play significant roles in this development. The growing sense of nationalism within states and the concomitant consequence of prioritizing their respective national interests led to the use, by these states, of international law as an instrument of justification. When international law is used this way, politics, and law inevitably confluence to serve the interests of those states with strong national objectives that they seek to achieve in any way possible. International trade has become very essential in international relations more than ever while it at the same time is affected by the political decisions of states at different levels. When the World Trade Organization was established (January 1, 1995), its first aim was to institutionalize the international trade relation among states so that more trade liberalization and integration would be achieved. It has been doing a remarkable job in working towards a more integrated world through its laws, systems, and institutions. The WTO Dispute Settlement System, with its establishing agreement (Dispute Settlement Understanding) and adjudicating bodies, is such a crucial system of the WTO with a good reputation in the past two decades. It has a complex procedure consisting of both political negotiation and adjudication in the judicial process. This paper limits itself to examining how political decisions by Member states within the WTO affect the WTO dispute settlement system’s progress to ‘judicialization’ of its adjudication process.